Peran Badan Penanggulangan Bencana Daerah Provinsi Sumatera Selatan dalam Meningkatkan Kinerja Satuan Tugas untuk Menanggulangi Bencana Kebakaran Hutan dan Lahan (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Forest and land fires must be anticipated early to prevent them from becoming major disasters that are difficult to control and fatal to the environment, health, and socio-economic life of the community. South Sumatra is a province with a high level of forest fire risk. This has become a concern for the Provincial Government in carrying out disaster mitigation through the Regional Disaster Management Agency (BPBD). This study highlights the role of BPBD in improving the performance of the Forest and Land Fire Task Force. The purpose of the study is to analyze the role of BPBD in strengthening the role of the Task Force in managing forest and land fire disasters. The study used a descriptive qualitative method with data collection techniques through observation, in-depth interviews, and data triangulation. The results of the study indicate that BPBD has played a fairly good role in forest and land fire management efforts, although it still faces obstacles such as limited human resources, infrastructure, and low public awareness in protecting the environment. BPBD has taken various strategic steps, such as developing SOPs for disaster management also a disaster information system, and conducting cross-sectoral coordination with the Health and Public Works Departments. Furthermore, community involvement is also carried out through the formation of forest and land fire awareness communities, outreach programs, and monitoring of fire-prone areas. BPBD also monitors preparedness and post-disaster recovery. This collaborative effort is expected to encourage sustainable and effective forest and land fire prevention, particularly during the dry season.